Solar heater box - Elbashier Elhada, Ragaa Mohammed; Muhamad Awang, Rita; Grozescu, Ionel Valeriu; Omar, Dzolkhifli; Sinniah, Uma Rani; Gnanasegaram, Manjeri (Universiti Putra Malaysia Press, 2013)
stored-product insects at high densities can consume a considerable amount of grains and pulses. Hence it could cause losses which arenestimated to be between 10-50%. Infestation of stored products by storage insect pests may result in reduction of nutrient, weight and quality of the product, in particular germination. They maybe vectors of bacteria and other pathogenic protozoa that carry diseases.